Distributed leadership and digital collaborative learning: A synergistic relationship? - Alma Harris; Michelle Jones; Suria Baba (2013)
This paper explores the synergy between distributed leadership and digital collaborative learning. It argues that distributed leadership offers an important theoretical lens for understanding and explaining how digital collaboration is best supported and led. Drawing upon evidence from two online educational platforms, the paper explores the challenges of leading and facilitating digital collaborative learning. The paper concludes that distributed leadership is integral to effective digital collaboration and is an important determinant of productive collaboration in a virtual environment.